Analisis Efektifitas Mesin/Alat Pabrik Gula Menggunakan Metode Overall Equipments Effectiveness - Subiyanto Subiyanto (Jurnal Teknik Industri: Jurnal Keilmuan dan Aplikasi Teknik Industri, 2014)
The national sugar production capability especially of the state owned sugar factory tends to decrease while demand increases.   To overcome the problem, government has issued the presidential Decree No. 5/2010 and declared a revitalization program of sugar industry as a priority development program. The Ministry of Industry has implemented the program by restructuring the sugar factory's machinery/equipments.  Since there are many of factories (51 units) and the budget is limited, the ministry should be selective as to which factories need to be restructered, and therefore the program shoud be supported by prior information about the machinery efficiency status of each factory. To provide those information,  this study applies the application of the Overall Equipment Effectiveness (OEE) method on 39 state owned sugar factories.  The results indicate that the everage rate of OEE for the 39 sugar factories for the year of 2010 to 2012 is 61.28% (best practice: 77.4%), while Availability, Performance, and Quality is 86.43%, 91.39%, and 77.02% respectively. The study also identifies 19 worst factories in efficiency, and therefore recommends those factories as priority to be restructured.